Loss of a water-mediated network results in reduced agonist affinity in a beta(2)-adrenergic receptor clinical variant - Nikte, V. Siddhanta; Sonar, Krushna; Tandale, Aditi; Joshi, Manali; Sengupta, Durba (Biochimica ET Biophysica Acta-Proteins and Proteomics, 2021)
The beta(2)-adrenergic receptor (beta(2)AR) is a member of the G protein-coupled receptor (GPCR) family that is an important drug target for asthma and COPD. Clinical studies coupled with biochemical data have identified a critical receptor variant, Thr164Ile, to have a reduced response to agonist-based therapy, although the molecular mechanism underlying this seemingly ``non-deleterious'' substitution is not clear. Here, we couple molecular dynamics simulations with network analysis and free-energy calculations to identify the molecular determinants underlying the differential drug response. We are able to identify hydration sites in the transmembrane domain that are essential to maintain the integrity of the binding site but are absent in the variant. The loss of these hydration sites in the variant correlates with perturbations in the intra-protein interaction network and rearrangements in the orthosteric ligand binding site. In conjunction, we observe an altered binding and reduced free energy of a series of agonists, in line with experimental trends. Our work identifies a functional allosteric pathway connected by specific hydration sites in beta(2)AR that has not been reported before and provides insight into water-mediated networks in GPCRs in general. Overall, the work is one of the first step towards developing variant-specific potent and selective agonists.
Keywords: beta(2)-Adrenergic receptor; G protein coupled receptor; GPCR; molecular dynamics; Pharmacogenetics; SNP